2017
DOI: 10.21873/invivo.11180
|View full text |Cite
|
Sign up to set email alerts
|

The Human Mesenchymal Stem Cells and the Chick Embryo Chorioallantoic Membrane: The Key and the Lock in Revealing Vasculogenesis

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…From a tissue engineering perspective, the CAM contains mesenchymal cells which show ‘stemness’ to differentiate, depending on the environment and factors applied. 82 , 83 These cells are important because they allow the interaction between exogenous cells applied to the CAM and resident avian cells, leading to differentiation towards vascular structures, changes in cell phenotype and tumour cell angiogenic mechanisms to be studied. 82 , 83 The mesenchymal cells within the CAM can also offer insights into cell differentiation and recruitment when acellular constructs are applied to the CAM surface.…”
Section: Bone Tissue Engineeringmentioning
confidence: 99%
“…From a tissue engineering perspective, the CAM contains mesenchymal cells which show ‘stemness’ to differentiate, depending on the environment and factors applied. 82 , 83 These cells are important because they allow the interaction between exogenous cells applied to the CAM and resident avian cells, leading to differentiation towards vascular structures, changes in cell phenotype and tumour cell angiogenic mechanisms to be studied. 82 , 83 The mesenchymal cells within the CAM can also offer insights into cell differentiation and recruitment when acellular constructs are applied to the CAM surface.…”
Section: Bone Tissue Engineeringmentioning
confidence: 99%
“…Chick embryo chorioallantoic membrane (CAM) is well known as a powerful experimental tool for the study of normal and pathologic angiogenesis, because of its high vascular network [13,14]. Additionally, CAM is an embryonic tissue lacking an immune system and having mesenchymal cells with stem like potential able to differentiate depending on a specific microenvironment [15,16]. Based on the previously described features, CAM is a reliable in vivo model for testing the behavior of normal and pathologic tissues (as cultured cells or malignant tumors) [17,18], of different drugs and antibodies [19,20], or of a variety of biomaterials implanted on its surface [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, hMSC induced a more intense angiogenic response, but a reduced vasculogenic reaction. Interestingly, when implanted alone onto CAM, hMSC determined an intense vasculogenic reaction, in addition to the angiogenic response (12), which means that MCF-7 have the ability to modulate the involvement of hMSC in neovessel formation. hMSC were demonstrated to enhance the de novo formation of stable vasculature by endothelial colony-forming cells in surrogate models of vasculogenesis in vitro and in vivo (3), in our study cMSC being the source for the endothelial colony-forming cells.…”
Section: Discussionmentioning
confidence: 99%
“…Using the CAM model, we demonstrated that MCF-7 seeded onto CAM recruit the mesenchymal cells from the CAM mesoderm and induce their differentiation towards myofibroblast-like or vasculogenic lineage, turning the mesoderm of the CAM into a surrogate tumor stroma (11). Further on, after the implantation onto CAM, hMSC induce vasculogenesis, by switching to an endothelial-like nonproliferative phenotype, but also by stimulating the chicken MSC from the mesoderm (cMSC) to acquire a vasculogenic and pericyte-like phenotype and to organize into cord/capillary like structures (CLS) (12).…”
mentioning
confidence: 99%